Um segmento menos elitizado da rede privada de ensino: três escolas no município de Contagem - Ana Rita Siqueira (2016)
The study develops from the empirical finding based on data from INEP/MECs Censo Escolar (school census) that in the last years in Brazil there has been a continuous growth in the number of enrolments in primary and secondary education of private schools, which apparently could be related with the recent process of economic rise of a segment of the lowest social classes in the country. On the other hand, there is a consensus in public opinion (as well as in the scientific realm) that Brazilian private schools students mostly come from the elites and the most privileged fractions of the middle class. This indicates there is some unawareness regarding the internal heterogeneity existing in the broader universe of private educational institutions, especially those which offer more affordable fees, and, therefore, admit families which come from less privileged social classes. The research aimed at learning about the characteristics of this segment of private educational institutions. In order to do this, three institutions at the city of Contagem/MG have been investigated. The schools were selected in view of the monthly fees. The instruments used in the research were the direct observation of the operating establishment and a semi-structured interview with the schools professionals and families. The results indicated the existence of some common characteristics among the three cases investigated, regarding: familys origin and management, restrict physical structure and material-pedagogical assets, human resources marked by multi-functionality, closeness in the family-school interaction, special care with students safety and with discipline in the pedagogical routine, implicit religiousness and inclusive education.